2021
DOI: 10.1016/j.bioactmat.2021.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Poly(l-glutamic acid)-cisplatin nanoformulations with detachable PEGylation for prolonged circulation half-life and enhanced cell internalization

Abstract: PEGylation has been widely applied to prolong the circulation times of nanomedicines via the steric shielding effect, which consequently improves the intratumoral accumulation. However, cell uptake of PEGylated nanoformulations is always blocked by the steric repulsion of PEG, which limits their therapeutic effect. To this end, we designed and prepared two kinds of poly( l -glutamic acid)-cisplatin (PLG-CDDP) nanoformulations with detachable PEG, which is responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…On the one hand, the circulation time of PEG‐pH e ‐PLG‐Pt and PEG‐MMP‐PLG‐Pt is much longer than that of PLG‐Pt. On the other hand, the PEG on the surface is detached due to pH e or MMP‐sensitive linkage to increase intratumoral CDDP retention and cellular uptake upon reaching tumor tissue (Figure 9b) (Jiang et al, 2021). Hence, the detachable‐polymer strategy exhibits promising prospects for the clinical application of PDC nanoparticles.…”
Section: Novel Approaches Of Nanopdcs Based On Capirmentioning
confidence: 99%
“…On the one hand, the circulation time of PEG‐pH e ‐PLG‐Pt and PEG‐MMP‐PLG‐Pt is much longer than that of PLG‐Pt. On the other hand, the PEG on the surface is detached due to pH e or MMP‐sensitive linkage to increase intratumoral CDDP retention and cellular uptake upon reaching tumor tissue (Figure 9b) (Jiang et al, 2021). Hence, the detachable‐polymer strategy exhibits promising prospects for the clinical application of PDC nanoparticles.…”
Section: Novel Approaches Of Nanopdcs Based On Capirmentioning
confidence: 99%
“…One study investigated Poly(l-glutamic acid)-CP (PLG-Pt) NP with detachable PEG conjugated to the surface with MMP-2/9-cleavable substrate PLGLAG (PEG-MMP-PLG-Pt). DePEGylation of these NP was triggered in the OvCa microenvironment, increasing tumor cell uptake of CP, while maintaining the PEG layer in normal tissues [ 251 ]. While the body weight of the free CP group fell, the weights were nearly unchanged in the PEG-MMP-PLG-Pt cohort, demonstrating the reduction in off-target side effects in addition to increased anti-tumor apoptotic activity and survival time.…”
Section: Protease Targeting Nanomedicine In Ovcamentioning
confidence: 99%
“…Dose-dependent cytotoxicity of CUR-PEI-K14/p53 and decreased CP resistance with the addition of the polymer conjugate. [ 248 ] MMP-2/9 Nanocomplexes of PLG-CP with detachable PEG conjugated to pH (pHe)-responsive 2-propionic-3-methylmaleic anhydride-derived amide bond OR MMP-cleavable peptide PLGLAG (PEG-pHe-PLG-Pt and PEG-MMP-PLG-Pt) BALB/c nude mice with IP OVCAR8 xenograft Overcome steric repulsion of PEG at the site of tumor to increase intratumoral uptake of CP and improve anti-tumor activity [ 251 ] Cathepsin B Self-assembling drug conjugate of Cathepsin B-specific cleavable peptide (FRRG) and DOX stabilized with pluronic F68 (termed PNPs) BALB/c nude mice with HEYA8 IP xenografts (POX) OR BALB/c with platinum-resistant patient-derived subrenal capsule xenografts (PDX) PNP increased IC 50 in normal tissue cell culture of PNP vs.free DOX, suggesting minimizing off-target effects; PNP showed decreased major organ absorption and increased persistence in the peritoneal cavity vs. free DOX; PNP showed enhanced tumor penetration vs. free DOX; PNP treated mice had prolonged survival over 30 days vs. free DOX which had death at 19 days due to chemotoxicity [ 124 ] …”
Section: Protease Targeting Nanomedicine In Ovcamentioning
confidence: 99%
“…Poly­(glutamic acid) (PGA) is a kind of biocompatible and biodegradable synthetic polypeptide. The pendant carboxylic acid groups of PGA can be readily modified to obtain multifunctional derivatives. In this study, we reported an acid-activatable and PGA-based nanoparticle (NP) for fluorescence imaging (FI)-guided precise PDT of the tumor. The polypeptide NPs not only possesses diagnosis and therapeutic property but also could be used as a versatile platform for tumor-specific drug delivery.…”
Section: Introductionmentioning
confidence: 99%